ОСНОВНІ ТЕНДЕНЦІЇ РОЗВИТКУ ЕНЕРГЕТИКИ УКРАЇНИ - Карп, І.М. (Інститут електродинаміки НАН України, Київ, 2018)
The balance between production and consumption of energy is one of the priority goals of the electric power industry in Ukraine's energy strategy. Electricity consumption in Ukraine is estimated at 120 billion kWh. The main consumers are the population, metallurgy, public utilities and transport (30, 25.13 and 6 percent, respectively). Changes in volumes of consumption can occur due to increased melting of electric steel and the production of electric vehicles. The global trend in generation is the increase in the share of decentralized energy from renewable sources, fuel cells and improved gas engines. A technological breakthrough in the use and transport of electricity is associated with the development of means of accumulation. In recent years, the cost of batteries has decreased and their power has increased. This will lead to their wide application in the utility sphere and energy systems. There will be no need to build peak capacities and pumped storage stations. There are risks in meeting the country's needs for hydrocarbon fuels. The main risk of Ukrainian energy is the danger of being out of technological progress. References 7, table 1.